2016
DOI: 10.1111/lam.12576
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hungarian mushrooms for antibacterial activity and synergistic effects with standard antibiotics against resistant bacterial strains

Abstract: In this study, 160 organic (n-hexane, chloroform and 50% methanol) and aqueous extracts of 40 mushroom species were submitted to antibacterial screening assay. The antibacterial capacity of 18 species has been examined for the first time. Nineteen extracts of 16 species showed antibacterial effects with moderate to high potential. The extracts of Fistulina hepatica, Tapinella atrotomentosa and Rhodocybe popinalis exhibited not only broad antibacterial spectrum, but also synergistic activity with cefuroxime aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…[22]. Moreover, the crude extract showed high synergistic effects in combination with cefuroxime against MRSA [116,125].…”
Section: Fistulina Hepatica (Schaeff)mentioning
confidence: 94%
See 3 more Smart Citations
“…[22]. Moreover, the crude extract showed high synergistic effects in combination with cefuroxime against MRSA [116,125].…”
Section: Fistulina Hepatica (Schaeff)mentioning
confidence: 94%
“…), commonly known as beefsteak fungus, is a wild edible fungus belonging to the family Fistulinaceae [95]. It is distributed in temperate and subtropical hardwood forests of China, Thailand, Hungary, Portugal [4,58,115,116], and other European countries. Two novel triacetylene derivatives have been isolated from the fruiting bodies and named cinnatriacetins A (37) and B (38) [117].…”
Section: Fistulina Hepatica (Schaeff)mentioning
confidence: 99%
See 2 more Smart Citations
“…In our search for higher mushrooms with antibacterial activity we previously demonstrated that several species native to Hungary exerted notable activity on Gram-positive and negative bacteria. Among these the extracts of Tapinella atrotomentosa (Batsch) Šutara revealed not only a broad-spectrum antimicrobial activity on Gram-positive and negative pathogens, but demonstrated also a significant inhibitory activity against resistant bacterial strains [ 2 ]. T. atrotomentosa —velvet rollrim by its vernacular name—is a wood-rotting mushroom belonging to the Tapinellaceae family.…”
Section: Introductionmentioning
confidence: 99%